2014
DOI: 10.1038/aps.2014.11
|View full text |Cite
|
Sign up to set email alerts
|

HapMap-based study on the association between MPO and GSTP1 gene polymorphisms and lung cancer susceptibility in Chinese Han population

Abstract: Aim: Myeloperoxidase (MPO) and glutathione S-transferase pi 1 (GSTP1) are important carcinogen-metabolizing enzymes. The aim of this study was to investigate the association between the common polymorphisms of MPO and GSTP1 genes and lung cancer risk in Chinese Han population. Methods: A total of 266 subjects with lung cancer and 307 controls without personal history of the disease were recruited in this case control study. The tagSNPs approach was used to assess the common polymorphisms of MOP and GSTP1 genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The stratified analysis by histological type of lung cancer revealed a significant difference in the frequency of the susceptible GSTP1 genotype, non-A/A, between the control group and lung squamous cell carcinoma group; and that subjects with the GSTP1 mutant allele had a higher risk of lung squamous cell carcinoma (OR=2.31, 95% CI: 1.180-4.512, P= 0.015), which is consistent with the findings of Ryberg et al (3). As for lung adenocarcinoma, GSTP1 exon 5 polymorphisms were not found to be associated with it in both a previous study (1) and the present study. It is known that lung squamous cell carcinoma mostly originates from the large bronchi, while lung adenocarcinoma mostly originates from peripheral lung tissue.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The stratified analysis by histological type of lung cancer revealed a significant difference in the frequency of the susceptible GSTP1 genotype, non-A/A, between the control group and lung squamous cell carcinoma group; and that subjects with the GSTP1 mutant allele had a higher risk of lung squamous cell carcinoma (OR=2.31, 95% CI: 1.180-4.512, P= 0.015), which is consistent with the findings of Ryberg et al (3). As for lung adenocarcinoma, GSTP1 exon 5 polymorphisms were not found to be associated with it in both a previous study (1) and the present study. It is known that lung squamous cell carcinoma mostly originates from the large bronchi, while lung adenocarcinoma mostly originates from peripheral lung tissue.…”
Section: Discussionsupporting
confidence: 90%
“…GSTP1 enzymes with a Val allele in exon 5 have a significantly decreased enzymatic activity, while those with a Val allele in exon 6 have no significant reduction in activity. Moreover, GSTP1 exon 5 polymorphisms have been found to be associated with lung cancer risk, whereas GSTP1 exon 6 polymorphisms have not been found to be correlated (1,2).…”
Section: Introductionmentioning
confidence: 97%
“…The analysis of SNPs rs1695 and rs2853676 of GSTP1 and Telomerase Reverse Transcriptase (TERT) genes respectively in 301 samples and 302 control samples Gliomas in Chinese patients showed a positive association for susceptibility to develop this neoplasm, therefore, could be considered risk factors for development gliomas (Li et al 2012). Gu et al (2014) analyzed the SNP rs7208693 of the Myeloperoxidase -MPO gene and haplotype SNPs rs1695, rs4891, rs762803 and rs749174 of the GSTP1 gene in 266 samples of lung câncer and 307 controls without personal history of the disease were recruited in this study in Chinese Han population. Haplotype SNPs rs1695, rs4891, rs762803 and rs749174 of the GSTP1 gene exhibited an association with lung cancer susceptibility in smokers in the overall population and in the studied subgroups but not the MPO SNP rs7208693 (Gu et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Gu et al (2014) analyzed the SNP rs7208693 of the Myeloperoxidase -MPO gene and haplotype SNPs rs1695, rs4891, rs762803 and rs749174 of the GSTP1 gene in 266 samples of lung câncer and 307 controls without personal history of the disease were recruited in this study in Chinese Han population. Haplotype SNPs rs1695, rs4891, rs762803 and rs749174 of the GSTP1 gene exhibited an association with lung cancer susceptibility in smokers in the overall population and in the studied subgroups but not the MPO SNP rs7208693 (Gu et al 2014). Xu et al (2012) studied 929 diagnostic GC patients in China and found a positive association between the SNPs rs1695 of the GSTP1 gene and rs4880 of the SOD2 gene to gastric carcinogenesis in this population.…”
Section: Resultsmentioning
confidence: 99%
“…These con icting results suggest that ethnic differences in GSTP1 genetic susceptibility may affect the development of GC with epigenetic interactions of environmental factors and that the relevance of GSTP1 genetic variants regarding GC risk needs to be con rmed in the future. Among the ve GSTP1 polymorphisms in this study, four (rs749174, rs1871042, rs4891, and rs947895) have been investigated by only a few studies in the context of lung cancer and asthma, and their associations with GC risk have yet to be determined (63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%